Direct foreign investment in Singapore. - Ang, Cheow Leng (2014)
Singapore's economy is heavily relying on direct foreign investment (DFI) to grow. The magnitude of DFI had a fact increased more than three times, from $11.2m at the end of 1980 to $41.1m at the end of 1989 [DOS, 1992a]. This is a very significant figure for a small country like Singapore. It is thus interesting to discuss various issues with regard to DFI which are of major concern to Singapore.